Strukturasi Adaptif Komunikasi Organisasi pada Key Opinion Leader Specialist dalam Komunitas Kreatif Digital - Silvi Andri Yani; Novi Andayani Praptiningsih; Yulia Rahmawati (Communicology: Jurnal Ilmu Komunikasi, 2026)
ABSTRACT Introduction: Changes driven by digital transformation in the creative industry have encouraged the formation of adaptive knowledge systems in the work practices of KOL Specialists within the Beauty Channel creative community. Objective: This study aims to analyze the process of adaptive structuration of knowledge systems among KOL Specialists in the Beauty Channel creative community. Methods: This research employs a descriptive qualitative approach with a case study method and a constructivist paradigm. It uses Adaptive Structuration Theory by DeSanctis and Poole. This study provides an update by integrating the adaptive structuration perspective with knowledge systems in the context of KOL Specialist work within digital creative communities, which remains underexplored in organizational communication studies focusing on influencer marketing. Results: The findings show that the organizational structure in Beauty Channel is formed through the interaction between formal rules such as KPIs, SOPs, and campaign workflows and the adaptive practices carried out by KOL Specialists in responding to brand dynamics, creators, and trends in the beauty industry. The knowledge system develops through internal discussions, regular evaluations, the use of digital communication media, and cross-team collaboration that supports collective learning. In addition, values of sensitivity and inclusivity within the creative community strengthen the sustainability of work practices. Conclusion: This study demonstrates that adaptive structuration plays an important role in shaping the knowledge system in the Beauty Channel creative community through the interaction between formal rules and adaptive work practices. ABSTRAK Pendahuluan: Perubahan akibat transformasi digital dalam industri kreatif mendorong terbentuknya sistem pengetahuan yang adaptif dalam kerja KOL Specialist di komunitas kreatif Beauty Channel. Tujuan: untuk menganalisis proses penstrukturan adaptif sistem pengetahuan pada KOL Specialist di komunitas kreatif Beauty Channel. Metode penelitian: menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus dan paradigma konstruktivisme. Penelitian ini menggunakan Teori Strukturasi Adaptif dari DeSanctis dan Poole. Penelitian ini memiliki pembaruan dalam integrasi perspektif sturkturasi adaptif dengan sistem pengetahuan pada konteks kerja KOL Specialist komunitas kreatif digital yang masih kurang diminati untuk dikaji dalam studi komunikasi organisasi yang berfokus pada influencer marketing. Hasil penelitian: menunjukkan bahwa struktur organisasi di Beauty Channel terbentuk melalui interaksi antara aturan formal seperti KPI, SOP, dan alur kampanye dengan praktik adaptif yang dilakukan KOL Specialist dalam menghadapi dinamika brand, creator, dan tren industri kecantikan. Sistem pengetahuan berkembang melalui diskusi internal, evaluasi rutin, penggunaan media komunikasi digital, serta kolaborasi antar tim yang mendukung pembelajaran kolektif. Selain itu, nilai sensitivitas dan inklusivitas dalam komunitas kreatif turut memperkuat keberlanjutan praktik kerja. Kesimpulan: Penelitian ini menunjukkan bahwa strukturasi adaptif berperan penting dalam pembentukan sistem pengetahuan di komunitas kreatif Beauty Channel melalui interaksi antara aturan formal dan praktik adaptif kerja.